Evaluation of The Ability of Bidara Leaf Extract (Zizipus mauritiana Lam.) as A Natural Preservative in Broiler Chicken Meat - M, Komaruddin; Miwada, I N.S.; Lindawati, S. A (Jurnal Peternakan Tropika; Vol 7 No 2 (2019), 2019)
Bidara leaf extract used in this study functions as an antibacterial. The aim of this study was to evaluate the ability of bidara leaf extract as an anti-bacterial and its effect on the characteristics ofchicken meat Broiler. This study used a completely randomized design with four treatments of bidara leaf extract material (0% (control), 10%, 15%, and 20%) and four replications. The variables observed included the value of pH, water content, water binding capacity, color, flavour, and total bacteria. The results showed that leaf extract bidara 10% to 20% can improve water binding ability (DIA) from 27.70 to 36.67; followed by a decrease in total bacteria from 2.23x10 7 to 1.1x10 7 ; with water content increasing from 76.29 to 77.99; but at pH it has decreased from 6.66 to 5.99. The conclusion of this study is that bidara leaf extract can be a natural preservative inchicken meat broiler. Keywords : bidara leaf extract, natural preservative, broiler chicken meat.